Design Media Learning Digital Game Based Learning (DGBL) Based on Quizizz in Basic Electronics Course - Rus Tsunami, Halimah; Lastya, Hari Anna (PTE FTK UIN Ar-Raniry, 2026)
This study aims to design and test the feasibility of Digital Game-Based Learning (DGBL) learning media based on the Quizizz application in the Basic Electronics course. The research method used is Research and Development (R&D) with a 4D development model. In the define stage, an analysis of needs, student characteristics, learning outcomes, and learning problems is carried out. The design stage is carried out through the preparation of quiz designs, selection of Quizizz features, preparation of assessment instruments, and adjustment of materials to learning indicators. The develop stage produces interactive quiz media, and is tested on a limited basis with students through a response questionnaire. The validation results show that the learning media obtained a feasibility percentage of 94% from material experts and 90% from media experts with a very feasible category. Meanwhile, the results of student responses obtained an overall percentage of 84.58% with a very good category. These findings indicate that the Quizizz-based DGBL learning media is worthy of being used as an alternative learning media. This media is able to support conceptual understanding, increase motivation, strengthen student involvement, and encourage independent learning in an interactive and fun way.